Biogeographic diversification of Eranthis (Ranunculaceae) reflects the geological history of the three great Asian plateaus. Issue 1948 (14th April 2021) - Xiang, Kun-Li; Erst, Andrey S.; Yang, Jian; Peng, Huan-Wen; Ortiz, Rosa del C.; Jabbour, Florian; Erst, Tatyana V.; Wang, Wei
Abstract : The evolutionary history of organisms with poor dispersal abilities usually parallels geological events. Collisions of the Indian and Arabian plates with Eurasia greatly changed Asian topography and affected regional and global climates as well as biotic evolution. However, the geological evolution of Asia related to these two collisions remains debated. Here, we used Eranthis, an angiosperm genus with poor seed dispersal ability and a discontinuous distribution across Eurasia, to shed light on the orogenesis of the Qinghai–Tibetan, Iranian and Mongolian Plateaus. Our phylogenetic analyses show that Eranthis comprises four major geographical clades: east Qinghai–Tibetan Plateau clade (I-1), North Asian clade (I-2), west Qinghai–Tibetan Plateau clade (II-1) and Mediterranean clade (II-2). Our molecular dating and biogeographic analyses indicate that within Eranthis, four vicariance events correlate well with the two early uplifts of the Qinghai–Tibetan Plateau during the Late Eocene and the Oligocene–Miocene boundary and the two uplifts of the Iranian Plateau during the Middle and Late Miocene. The origin and divergence of the Mongolian Plateau taxa are related to the two uplifts of the Mongolian Plateau during the Middle and Late Miocene. Additionally, our results are in agreement with the hypothesis that the central part of Tibet only reached an altitude of less than 2.3 km at approximately 40 Ma. This study highlights that organismal evolution could be related to the formation of the three great Asian plateaus, hence contributing to the knowledge on the timing of the key tectonic events in Asia.